Design and experiment of path tracking system for field management machine - HUANG Tengda; JIANG Pin; HU Wenwu; XIAO Feifei; WU Fan; LIU Zhanming (浙江大学学报. 农业与生命科学版)
In order to solve the problem of crop loss caused by the internal wheel difference when the front wheels of the field management machine were turned, this study proposed a path tracking algorithm based on the four-wheel steering field management machine. Taking the 3WPZ-750 field management machine as the research object, a set of path tracking control system was designed. First, the mechanical structure design of the research subject’s steering outriggers and the principle of the automatic steering hydraulic system were explained. Second, the technical route of the path tracking host computer control system based on the original control system was outlined. Then, based on the four-wheel steering model, a pure tracking algorithm was used for wheel steering angle control research. Finally, the path tracking control interface was written based on Microsoft integrated development environment (visual studio). Through its experimental platform, the straight path tracking and curved path tracking experiments were carried out on the cement pavement and the southern paddy field environment, respectively. The results showed that at the speed of 0.5 m/s, the field management machine had a path tracking error of 6.92 cm on the cement pavement, and its standard deviation was 4.84 cm; while the mean value of the path tracking error of the fixed curvature curve was 12.49 cm, and its standard deviation was 9.16 cm. At the speed of 0.2 m/s, on the southern paddy field, the mean value of the path tracking error was 2.25 cm, and its standard deviation was 1.35 cm; while the mean tracking error of the fixed curvature curve was 8.72 cm, and its standard deviation was 5.59 cm. The above results indicate that the path tracking algorithm proposed in this study can meet the needs of field management machines and field operations, and provide a basis for automatic driving of agricultural machinery.